“Isms” or the International Criminal Court and its place in the international legal order – review of a quarter of century - Kovács, Péter (The ICC at 25: Lessons Learnt, 2025)
This article provides an overview of the twenty-five-year existence of the International Criminal Court (ICC). The ICC has faced various challenges since its establishment. Some of these challenges were partly rooted in the work done in the final days of the Rome Diplomatic Conference, where a mutually acceptable text had to be forged on the basis of often conflicting textual proposals. Other challenges emerged with the changes in the political will of several states. The chambers of the ICC tried to establish a coherent jurisprudence able to cope with the eventual imperfections of the Rome Statute. While jurisprudential practice can help identify appropriate content for the complex formulas, which are sometimes the fruit of diplomatic ambiguity, political challenges are more difficult to overcome. Politicalactors cited concerns regarding “anti-Africanism”, lack of efficiency, and “politicisation”—critiques often intended to conceal a lack of genuine co-operation or even animosity towards independent international control. As this article shows, an important part of the legacy of the International Criminal Tribunal for the former Yugoslavia (ICTY) lies in the autonomous development of ICC jurisprudence and the specificities of common and continental law, as well as “criminal law” and “public international law”. The relevance of the ICC cannot be measured in the number of adjudicated cases and condemned perpetrators alone. The impact of the ICC on reparation and assistance to victims and the uniform interpretation of international criminal law at various law faculties and military academies cannot be overlooked. Keywords: cases and situations, common law, complementarity, co-operation, continental law, human rights, ICC, ICTY, ICTR, international criminal law, international humanitarian law, jurisprudential coherence and reforms, Practice Manual, procedural guarantees, victim’s reparation